Article RETRACTED due to malpractice Intention to Use AI for Academic Purposes among Physical Education Students - Benny, Alex; J., Solomon Thangadurai (Retos, 2026)
This study explores the intention to use Artificial Intelligence for academic purposes among physical education students by extending the Technology Acceptance Model (TAM). It incorporates variables such as trust in AI, ethical concerns, perceived usefulness, ease of use, and subjective norms. The findings reveal that students' trust in AI and positive ethical perceptions significantly influence their attitudes and intentions to adopt AI tools for learning.